Learning By Tracing Worked Examples. Issue 2 (26th September 2015) - Ginns, Paul; Hu, Fang‐Tzu; Byrne, Erin; Bobis, Janette
Summary: Cognitive load theorists have only recently begun to test the role of the body in learning. Tracing the index finger over the surface of instructions while reading, an embodied pedagogy based on Montessori's sandpaper letters, may hold substantial promise for learning by reducing cognitive load. Two experiments tested whether students who traced their index fingers against paper‐based worked example instructions in triangle geometry (Experiment 1; N = 52) and order of operations (Experiment 2; N = 54) would perform better on a subsequent test than students who only studied the materials visually. Students in the tracing condition outperformed the non‐tracing condition on transfer problems in both Experiment 1 (d = .78) and Experiment 1 (d = .50), but hypotheses regarding self‐reports of cognitive load during testing were not supported. Implications for research and practice are discussed. Copyright © 2015 John Wiley & Sons, Ltd.